Pertumbuhan dan Hasil Ubi Jalar dengan Pemberian Pupuk Kandang serta Uji Varietas Terhadap Cylas Formicarius - Azizah, Fida; Sulistyo, Ato; Subagiya, Subagiya (Agrotechnology Research Journal, 2018)
Sweet potato production enhancement efforts are limited by the constraints of one of these pests boleng (C. formicarius) and application of chemical fertilizers continuously. The research in field use Randomized Complete Block Design (RAKL) with two treatments. The varieties (Korea, Manohara, Madu) and manure (control, cow manure, chicken manure). While research in laboratory use 3 varieties and adult of C. formicarius. The result showed that granting of chicken manure on Manohara varieties give the best response on a length of stem, number of leaves, fresh weight and weight of tubers. Granting of cow manure on Manohara and Madu Varieties give the weight of tuber stricken is less than Korea varieties. Choice test in Manohara varieties show the high population while in no choice test show Korea Varieties have high population of C. formicarius.